2014
DOI: 10.1021/mp400455r
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Amorphous Statin: Solid-State NMR and Dielectric Studies on Dynamic Heterogeneity of Simvastatin

Abstract: Statins have been widely used as cholesterol-lowering agents. However, low aqueous solubility of crystalline statins and, consequently, reduced biovailability require seeking for alternative forms and formulations to ensure an accurate therapeutic window. The objective of the present study was to evaluate the stability of amorphous simvastatin by probing molecular dynamics using two nondestructive techniques: solid-state NMR and dielectric relaxation spectroscopy. Glassy simvastatin was obtained by the melt qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…Furthermore, formulation stability increases with increasing T g values ( Li et al, 2015 ). This is partly due to molecular mobility being a driving force for recrystallization ( Nunes et al, 2014 ). The lower the molecular mobility, the higher the degree of intermolecular interactions and the more stable the formulation ( Sibik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, formulation stability increases with increasing T g values ( Li et al, 2015 ). This is partly due to molecular mobility being a driving force for recrystallization ( Nunes et al, 2014 ). The lower the molecular mobility, the higher the degree of intermolecular interactions and the more stable the formulation ( Sibik et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The formulation has a high T g (i.e., 107 °C) because the KinetiSol process does not require plasticizers, which are known to decrease the system's T g ( DiNunzio et al, 2010 ). Recrystallization rates increase above the formulation's T g ; therefore, limiting molecular mobility promotes stability ( Nunes et al, 2014 ). Additionally, Keratichewanun et al reported that for homogenous samples (e.g., 59–4 and 59–5), the crystallization tendency is inversely proportional to the degree of drug–polymer interactions ( Keratichewanun et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the III and II forms are metastable at ambient temperature and, if present, will readily convert to form I, whose stability domain extends up to the fusion temperature. It should, nevertheless, be bear in mind that melting and quench cooling can lead to persistent amorphous phases, , or to chemical degradation, if the process is not carried out under inert atmosphere. The possibility of chemical degradation will be particularly critical if, for example, strategies to improve the solubility of simvastatin involving melting are considered.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out (Wenz, 1994) substrates complexed with CD are in a very heterogeneous environment and complexed and free molecules may undergo fast exchange processes. Future work includes the evaluation of the stability of the ABZ:citrate-␤-CD inclusion complex as previously described for a cholesterol-lowering drug (Nunes et al, 2014). This study will be performed by probing mobility in the kHz frequency range through spin-lattice relaxation time in the rotating frame measurements as a function of temperature.…”
Section: Cyclodextrinmentioning
confidence: 99%